2016
DOI: 10.1016/j.jtcvs.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and long-term outcomes of contemporary patients with bicuspid aortic valves

Abstract: Patients with BAV have a high prevalence of AV dysfunction and concomitant aortopathy. Undergoing surgery (AV replacement and/or repair ± AAR) was associated with a significantly lower incidence of death and/or dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 28 publications
2
64
1
2
Order By: Relevance
“…Few studies have reported on moderate to severe AR prevalence in BAV,6–8 12–14 but those showed a varied prevalence between 13% and 32%, probably representing community cohorts versus referral bias in the tertiary care settings. AR tends to present at a younger age when compared with AS, with a mean age around 45 years (vs 54 years for significant AS) 8. In a recent study of 1417 mostly asymptomatic patients (37% with BAV) with ≥III+ AR, there was significantly improved long-term survival following AV surgery, similar to that of an age-matched and gender-matched population 23…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Few studies have reported on moderate to severe AR prevalence in BAV,6–8 12–14 but those showed a varied prevalence between 13% and 32%, probably representing community cohorts versus referral bias in the tertiary care settings. AR tends to present at a younger age when compared with AS, with a mean age around 45 years (vs 54 years for significant AS) 8. In a recent study of 1417 mostly asymptomatic patients (37% with BAV) with ≥III+ AR, there was significantly improved long-term survival following AV surgery, similar to that of an age-matched and gender-matched population 23…”
Section: Resultsmentioning
confidence: 89%
“…Significant mixed AS and AR developed only in 1% of the patients in the study by Michelena et al 6 and was present in 3% of the patients in the study by Masri et al 8. Another recent study evaluated the outcomes of 251 patients with mixed moderate AS and AR, of which 38% had BAV 28.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, as demonstrated by the results of the current study and others pertaining to complex aortic root and ascending aortic surgeries, the most appropriate option would be to offer this only at high-volume experienced centers that have demonstrated excellent surgical outcomes, after shared decision making. 10,[36][37][38][39][40][41] These findings need prospective validation, especially in patients with an isolated BAV aortopathy.…”
Section: Discussionmentioning
confidence: 99%
“…9,14,17 On the contrary, prior data have suggested that ≈40% patients (including patients with BAV aortopathy) have an aortic diameter <5 cm at the time of presentation with type A dissection. 18 Furthermore, absolute aortic diameter cutoffs have inherent limitations, including failure to account for size/height, sex, 19,20 and irregular elliptical shape of the aorta (frequently observed in BAV 1,10 ). Therefore, previous reports have suggested indexing aortic dimensions using either body surface area (BSA) or height.…”
mentioning
confidence: 99%
“…Показатели выживаемости в отдаленном периоде в ФГБНУ «НИИ КПССЗ» сопоставимы с данными зару-бежной литературы [9][10][11][12].…”
Section: показатели выживаемости в группе механических и биологическиunclassified